Plasmonics: Refractory Plasmonics with Titanium Nitride: Broadband Metamaterial Absorber (Adv. Mater. 47/2014). (December 2014) - Li, Wei; Guler, Urcan; Kinsey, Nathaniel; Naik, Gururaj V.; Boltasseva, Alexandra; Guan, Jianguo; Shalaev, Vladimir M.; Kildishev, Alexander V.
<x xml:space="preserve">Abstract</x> Alternative plasmonic materials can withstand extreme temperatures, opening new frontiers in energy‐harvesting applications. A metamaterial based on titanium nitride, described by J. G. Guan, A. V. Kildishev, and co‐workers on page 7959, efficiently converts sunlight into heat, achieving temperatures greater than 1000 °C and it re‐radiates this energy in a narrow bandwidth for optimal absorption by a photocell. The near perfect absorption of the metasurface coupled with its thermal stability enables practical next generation solar thermo‐photovoltaic devices. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>